144 Predicting Recovery After a Spinal Cord Injury: The Role of Diffusion Basis Spectrum Imaging as a Biomarker of Corticospinal Tract Integrity. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Murphy, Rory K.J.; Gamble, Paul; Sun, Peng; Wang, Yong; Jacobs, Eileen; Song, Sheng-Kwei; Ray, Wilson Zachary
Abstract: INTRODUCTION: Currently, there is no noninvasive method to determine spinal cord integrity after a spinal cord injury (SCI) and, thus, a patient's potential for recovery. This is despite 253 000 people in the United States living with a SCI. Diffusion tensor imaging (DTI) measurement of spinal cord injury is significantly confounded by inflammation and tissue loss manifested in diffusion magnetic resonance imaging signal modeling as a spectrum of isotropic diffusion tensor components 1. To overcome these factors, we have developed a novel data-driven model-selection diffusion basis spectrum imaging (DBSI) 2 to more accurately delineate anisotropic signal sources. We hypothesized that DBSI acting as an axonal injury biomarker more accurately correlated with neurological disabilities in humans following an acute SCI and/or a chronic SCI than the current standard DTI biomarker. METHODS: A prospective non-randomized cohort of 27 spinal cord injury patients underwent imaging over a 2-year period. DBSI derived fractional anisotropy (FA), axial diffusivity (AD), radial diffusivity (RD), edema fraction and axonal density were correlated with clinically utilized grading scales including American Spinal Injury Association (ASIA) Score. RESULTS: Patients showed a decline in cross-sectional spinal cord area compared with a stable cord area in controls. Higher International Standards for Neurological Classification of SCI (ISNCSCI) scores at 12-months post-injury were associated with a reduced loss in cross-sectional spinal cord area and higher corticospinal FA encompassing the corticospinal tract at the cerebral peduncle. Compared with recovered ASIA grade E (ASIA-E) patients, severely injured ASIA grade A (ASIA-A) patients showed increased DTI radial (A: 0.32 E: 0.20, P < .05) and axial diffusivity (A: 1.1 E: 0.91, P < .05), increased DBSI water fraction (A: 0.11 E: 0.05, P < .05), decreased DTI (A: 0.84 E: 0.89, P < .05) and DBSI FA (A: 0.66 E: 0.74, P < .05), and decreased DBSI fiber ratio (A: 0.059 E: 0.071, P < .05). CONCLUSION: DBSI can delineate extensive upstream atrophic and microstructural changes of corticospinal axons occur due to Wallerian degeneration as indicated by reduced FA and axonal density after spinal cord injury, with greater reductions in axonal density relating to poorer recovery.